Overview of long non-coding RNA and mRNA expression in response to methamphetamine treatment in vitro. (October 2017) - Xiong, Kun; Long, Lingling; Zhang, Xudong; Qu, Hongke; Deng, Haixiao; Ding, Yanjun; Cai, Jifeng; Wang, Shuchao; Wang, Mi; Liao, Lvshuang; Huang, Jufang; Yi, Chun-xia; et al.
Abstract: Long non-coding RNAs (lncRNAs) display multiple functions including regulation of neuronal injury. However, their impact in methamphetamine (METH)-induced neurotoxicity has rarely been reported. Here, using microarray analysis, we investigated the expression profiling of lncRNAs and mRNAs in primary cultured prefrontal cortical neurons after METH treatment. We observed a difference in lncRNA and mRNA expression between the experimental and sham control groups. Using bioinformatics, we analyzed the highest enriched gene ontology (GO) terms of biological process, cellular component, and molecular function, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway and pathway network analysis. Furthermore, an lncRNA-mRNA co-expression sub-network for aberrantly expressed terms revealed possible interactions of lncRNA NR _ 110713 and NR _ 027943 with their related genes. Afterwards, three lncRNAs ( NR _ 110713, NR _ 027943, GAS5 ) and two mRNAs ( Ddit3, Casp12 ) were targeted to validate the microarray data by qRT-PCR. This presented an overview of lncRNA and mRNA expression profiling and indicated that lncRNA might participate in METH-induced neuronal apoptosis by regulating the coding genes of neurons. Highlights: Expression profiling of lncRNA and mRNA induced by methamphetamine was presented. ER stress may be crucial in neuronal apoptosis caused by methamphetamine. LncRNA may participate in apoptotic pathway in methamphetamine-induced neurotoxicity.